The Role of the Community in the Development of Culinary Tourism in West Sumataera - Novesar, Muhammad Refki; Hafid, Fauziah Sri Andria (CV. Rayyan Dwi Bharata, 2024)
Tourism is a vital economic sector in many countries with economic impact and activation in various sub-sectors. In Indonesia, tourism development, especially culinary, is a national priority. For this reason, it is necessary for the role of the West Sumatran community in developing and maintaining traditional culinary as part of West Sumatra's traditional cultural identity. With a focus on community participation, tourism development, and culinary sustainability, this research uses a qualitative approach. The results show that West Sumatran cuisine, such as rendang, has a central role in tourism attraction, reflects cultural heritage, and plays an important role in people's daily lives. Despite the challenges of globalization, the people of West Sumatra are actively involved in preserving and developing traditional culinary, creating jobs, and supporting the local economy. Thus, the close relationship between the community and traditional culinary forms a symbiosis that enriches the culture, identity and economy of the region.